Physical random analysis of Boolean chaos - Lishuang GONG; Erlin HOU; Haifang LIU; Kaikai LI; Yuncai WANG (Tongxin xuebao)
To analyze the physical randomness of Boolean chaos,the model for chaotic circuit system based on autonomous Boolean network was established.In addition,the equations of the Boolean network with phase noise were deduced.By considering the phase noise,the time for the growth of entropy for an ensemble of trajectories,called the memory time,was analyzed.It was demonstrated that Boolean chaos would be unpredictable after tens of nanoseconds,and less average memory time was required as the phase noise strength increased.It is shown that Boolean chaos has physical randomness because of phase noise and it also lays the theoretical foundation for the entropy source of true random number generator based on chaotic Boolean network.